Impact of Exposure to Natural and Built Environments on Positive and Negative Affect: A Systematic Review and Meta-Analysis - Yao, Wenfei; Chen, Fei; Wang, San; Zhang, Xiaofeng (Frontiers in Public Health, 2021)
There is an increasing evidence that natural environment provides substantial human emotional well-being benefits. The current study synthesized this body of research using meta-analysis and assessed the positive and negative affect of exposure to both natural and built environments. We searched four databases and 20 studies were included in the review. Meta-analysis results showed the most convincing evidence that exposure to the natural environment could increase in positive affect (SMD = 0.61, 95% CI 0.41, 0.81) and decrease in negative affect (SMD = -0.47, 95% CI -0.71, -0.24). However, there was extreme heterogeneity between studies and the risk of bias was high. According to the subgroup analysis, study region, study design, mean age of sample, sample size, type of natural and built environment were found to be important factors during exposure to the natural environment. The implications of these findings for existing theory and research were discussed. These findings will help to convince health professionals and policymakers to encourage residents to increase their exposure time spent in the natural environment, as well as encourage them to give due consideration to the creation, maintenance, and enhancement of existing natural environment in inadequate areas.